Pemberdayaan Kegiatan Ekstrakurikuler Sains untuk Penguatan Prestasi Siswa Sekolah Dasar Islam - Agustin, Adek; Lestari , Anggun Indah; Harianti, Evi; Marwan, Syaiful (BA: Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to explore the empowerment of science extracurricular programs as a strategy to improve student achievement in Islamic elementary schools. A descriptive qualitative method was used, with data collected through observation, interviews, and documentation. The subjects included upper-grade students, science club mentors, and school administrators. Findings reveal that well-structured science extracurricular activities significantly increase students’ interest and motivation in learning science. Activities such as simple experiments, group discussions, and science competitions help students develop critical thinking skills, curiosity, and teamwork. These programs not only improve academic outcomes, particularly in science subjects, but also foster essential character values like discipline, responsibility, and self-confidence. The study concludes that empowering science-based extracurricular activities can be an effective approach to enhancing the academic and personal growth of students. Schools are encouraged to provide sustainable support and innovation in extracurricular planning to ensure long-term educational benefits